1998
DOI: 10.1021/jp980685d
|View full text |Cite
|
Sign up to set email alerts
|

Kamlet−Taft Solvatochromic Parameters of the Sub- and Supercritical Fluorinated Ethane Solvents

Abstract: The Kamlet−Taft parameters describing the dipolarity-polarizability, π*, and hydrogen bond acceptor ability, β, for ethane and six fluorinated ethane solvents in the sub- and supercritical region of the phase diagram were measured using solvatochromic probe molecules. The measured ultraviolet electronic transitions of the solvatochromic probes in a given solvent were fitted to third-order polynomials in solvent density for all isotherms investigated. The values of π* and β were calculated for each of the solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…Solvatochromic probes have been used to quantify U for com-Ž . pressed solvents Lagalante et al, 1998 as well as traditional liquid solvents. The U values of HFE-7100 and Vertrel were determined from spectroscopic measurements based on the following system of probe molecules: 2-nitroaniline, 3-Ž .…”
Section: Determination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvatochromic probes have been used to quantify U for com-Ž . pressed solvents Lagalante et al, 1998 as well as traditional liquid solvents. The U values of HFE-7100 and Vertrel were determined from spectroscopic measurements based on the following system of probe molecules: 2-nitroaniline, 3-Ž .…”
Section: Determination Ofmentioning
confidence: 99%
“…fluorohexane, s 0.40 . Lagalante et al 1998 have reported the values of fluorinated ethanes to range from y1.2 to 0.5 as a function of density and arrangement of the fluorine atoms on the ethane backbone. The high value of 0.43 for Vertrel can be attributed to the acidity of the two hydrogen atoms in proximity to the large number of electronegative fluorine atoms.…”
Section: žmentioning
confidence: 99%
“…Supercritical fluids, however, have a tunable solvent strength as evidenced by the density-dependent dipolarity/polarizability of the solvent π 1 . [16][17][18][19][20] Therefore, any derived LSER approach for supercritical fluids will probably require additional density-dependent solvent terms. In a recent paper, we reported measurements of π 1 for six fluorinated ethanes including R143a.…”
Section: Introductionmentioning
confidence: 99%
“…The solvatochromic behaviors of THICZs and solvent‐solute interactions can be investigated by methods for instrumentation of linear solvating energy relationships conception projected by Kamlet and Taft. [ 21 ] The spectral profiles of the compounds (3 mg in 10 mL solvent) under investigation were prerecorded with six organic solvents with broad assortment of solvent parameters for instance dielectric constant ε, refractive index n and solvatochromic parametric quantity α, β, and π*. The spectra of THICZs ( 3a‐3f and 4) in diverse organic solvents are bestowed in Data S1, individually.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of solvent polarity and hydrogen bonding on the absorption spectra are interpreted by means of linear solvation energy relationship (LSER) using a Kamlet‐Taft equation. [ 21 ] νmax=ν0+++*, where ν max is maximum absorption wave number of the given compound processed experimentally, ν 0 was calculated by the regression method, the other parameters, that is, the Kamlet‐Taft coefficients a, b, and s was also calculated using regression analysis method (Table 2). Negative values of both s and b (Table 2) indicate that there is positive solvatochromism which means bathochromic shift with increase in solvent polarizability and solvent bond basicity.…”
Section: Resultsmentioning
confidence: 99%